Effect of controlled atmospheric conditions combined with salt acid immersion on trimmed young coconut qualities during cold storage. (June 2022) - Treesuwan, Khemmapas; Jirapakkul, Wannee; Tongchitpakdee, Sasitorn; Chonhenchob, Vanee; Mahakarnchanakul, Warapa; Moonmangmee, Somporn; Tongkhao, Kullanart
Abstract: Trimmed young coconut (TYC) contributes to global economic trade but is impacted by microbial and browning spoilage during the cold chain operation. TYCs were dipped in salt/acid solution (SA; 10% sodium chloride and 10% citric acid) and stored at 2 °C for 8 weeks in three different controlled atmosphere (CA) conditions with normal atmospheric condition as the control. Qualities and bacterial profiles of TYCs were determined. TYC treated with SA+CA (5% O2 + 7.5% CO2 ) showed the lowest average browning index of 29.13. Titratable acidity, total soluble solid content and pH ranged 0.026–0.071%, 6.86–8.96 °Brix and 5.38–6.51, respectively. Aerobic plate count and total yeast and mold counts were less than 4 log CFU/area of each shoulder, body and bottom area of TYCs. Leuconostoc mesenteroides and Pseudomonas sp. were undetected by PCR-DGGE analysis. Results suggested that SA+CA (5% O2 + 7.5% CO2 ) offered a non-allergenic hurdle technology to prolong the shelf life of TYC. Graphical Abstract: ga1 Highlights: Salt/acid solution and 5% O2 + 7.5% CO2 inhibited browning of TYC for 8 weeks. No fungi in TYC water treated with salt/acid solution and 5% O2 + 7.5% CO2 . L. mesenteroides and Pseudomonas sp. were undetected in TYC under CA condition.